2016
DOI: 10.1007/s00441-015-2348-8
|View full text |Cite
|
Sign up to set email alerts
|

Microcavity arrays as an in vitro model system of the bone marrow niche for hematopoietic stem cells

Abstract: In previous studies human mesenchymal stromal cells (MSCs) maintained the "stemness" of human hematopoietic progenitor cells (HPCs) through direct cell-cell contact in two-dimensional co-culture systems. We establish a three-dimensional (3D) co-culture system based on a custom-made chip, the 3(D)-KITChip, as an in vitro model system of the human hematopoietic stem cell niche. This array of up to 625 microcavities, with 300 μm size in each orientation, was inserted into a microfluidic bioreactor. The microcavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 47 publications
(55 reference statements)
0
36
0
1
Order By: Relevance
“…The small‐sized cavities allow secreted factors to accumulate more efficiently than in larger spaces, therefore attenuating autocrine signals over paracrine cues. Further exploiting a microcavity array, stromal cells were incorporated in a chip‐based 3‐D co‐culture of UCB hematopoietic cells favoring cell‐to‐cell contact through β‐catenin and N‐cadherin intercellular junctions and therefore contributing to preserve the primitiveness of hematopoietic progenitor cells in comparison to monolayer co‐cultures …”
Section: ‐D Co‐culture Of Hspc and Mscmentioning
confidence: 99%
“…The small‐sized cavities allow secreted factors to accumulate more efficiently than in larger spaces, therefore attenuating autocrine signals over paracrine cues. Further exploiting a microcavity array, stromal cells were incorporated in a chip‐based 3‐D co‐culture of UCB hematopoietic cells favoring cell‐to‐cell contact through β‐catenin and N‐cadherin intercellular junctions and therefore contributing to preserve the primitiveness of hematopoietic progenitor cells in comparison to monolayer co‐cultures …”
Section: ‐D Co‐culture Of Hspc and Mscmentioning
confidence: 99%
“…Various sorts of microwells have been engineered to confine distinct cell types in a common volume (Dusseiller et al, 2005) (Khademhosseini et al, 2006) (Moeller et al, 2008) (Lutolf et al, 2009) (Guldevall et al, 2010) (Minc et al, 2011)(Gobaa et al, 2011)(Müller et al, 2015. In such microwells, HSPC stemness could be maintained over several weeks in 3D co-cultures with mesenchymal stromal cells (Wuchter et al, 2016). In our culture model, we used a differential patterning approach to restrict cell-substrate adhesion to the bottom of the microwell only in order to prevent cells from escaping the well (Dusseiller et al, 2005;Ochsner et al, 2007) (Gobaa et al, 2011) and to enable high quality imaging.…”
Section: Resultsmentioning
confidence: 99%
“…A micro cavity array comprising 3x105 MSCs and 2x105 HSCs was cultivated under flow conditions (400µl/ min) for 14 days. Immunofluorescence, gene expression profiling with sqRT2-PCR and western blots revealed that the HSCs in the bioreactor throughout the entire cultivation period expressed CD34 whereas the expression was lost in control mono layers after 5 days indicating stem cell maintenance in the microcavity array system [103]. After a culture period of 21 days, it could be shown by single cell tracking and quantification of HSCs inside single microcavities that HSCs migrate in the cellular network of MSCs where they form two populations, one that resides in the upper region of the microcavity and one that migrates to the bottom of the microcavity where extensive proliferation can be observed and at the same time maintaining CD34-expression (unpublished results, Figure 4).…”
Section: Bioreactor Systemsmentioning
confidence: 99%